Т. 1; Сборник аннотированных фольклорных и бытовых текстов обско-енисейского языкового ареала - Фильченко А. Ю. Андрей Юрьевич; Потанина О. С. Ольга Сергеевна; Крюкова Е. А. Елена Александровна; Глазунов П. Ю.; Байдак А. В. Александра Владимировна; Максимова Н. П. Наталья Петровна; Федотова Н. Л. Надежда Леонидовна; Гусев В. Ю. Валентин Юрьевич; Лемская В. М. Валерия Михайловна; Токмашев Д. М. Денис Михайлович; Ким А. А. Антонина Александровна (Изд-во Ветер, 2010)
Заглавие с экрана